Marginalization strategies in Iraqi newspapers' coverage of the October 2019 protests “Paradigm” Module - Khamash, Halim Abdul Amir (ALBAHITH ALALAMI, 2023)
This study aims to inspect the marginalization strategies implemented by Iraqi newspapers, with a focus on the daily newspaper (Al-Sabah) and its coverage of the October 2019 protests in Iraq, by employing the “Paradigm” Module. The research is descriptive the researcher implemented a descriptive-analytical survey method by using a non-probability sampling represented by (74) issues of Al-Sabah newspaper and used (content analysis form) as a tool to analyze (93) news content related to the October protests.The Researcher reached several conclusions: 1- Al-Sabah newspaper mainly depends on “Economic Reforms” as a marginalization strategy in its news coverage of the October 2019 protests. 2- The newspaper focused mainly on the (official sources), ignoring protesters themselves, and limited its coverage to official sources, religious, and social figures. 3- Implementing the “conspiracy” strategy, consistent with the Iraqi government’s repeated arguments to marginalize the protests while promising to conduct investigations. 4- There are similarities between the “Paradigm” Module presented in this research and the Dardis, Frank E. “Paradigm” Module.